How Did We Develop a Photographic Guide of Biodiverse Food Plants to Support Food Consumption Studies?. Issue 2 (May 2023) - Ribeiro, Ially D. O.; Batista, Natalia A. D. N.; Cunha Lima, Severina Carla V.; Jacob, Michelle Cristine M.
This short take explains how we developed a photographic guide for assessing biodiversity in food consumption studies with taxonomy accuracy. To build the guide, we followed the "Guidelines on Assessing Biodiverse Foods in Dietary Intake Surveys" of the Food and Agriculture Organization (FAO) of the United Nations. As far as we know, this is the first tool developed in Brazil to support dietary surveys that consider food biodiversity. As researchers, this guide may help us make local biodiverse food more visible in food studies, improving our capacity to evaluate their contribution to nutritional and cultural outcomes.